Renewing creative work for business innovation: Architectural practice in the trading zone. Issue 4 (27th May 2021) - Stang Våland, Marianne; Svejenova, Silviya; Clausen, Rune Thorbjørn Jason
Abstract: How do organizations in creative industries renew creative work for business innovation? What challenges do they experience in the process? Drawing on an eight‐month ethnography in an architectural practice, this article suggests that renewal of creative work takes place in two main trading zones: a creative business trading zone of managers and architects trading with the conception of architectural practice as a business, and a creative process trading zone of architects and process facilitators trading with the process of architectural design. We show how resolving challenges within and moving across trading zones enables managers and architects to renew the architectural design process and establish renewal as a business innovation. The study advances the understanding of innovation in creative industries by proposing trading zones as arenas for negotiating art‐business tensions and 'tools' for renewing creative work, to make way for business innovation while preserving the autonomy of the creative professionals.